2003
DOI: 10.1614/0043-1745(2003)051[0231:matacb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

MON 37500 application timing affects cheat (Bromus secalinus) control and winter wheat

Abstract: Sixteen field experiments were conducted across Oklahoma to evaluate the effects of MON 37500 time of application on cheat control, and winter wheat injury and yield. Winter wheat injury from MON 37500 applied preemergence (PRE) was slight and was influenced by cumulative precipitation for 10 d after application. Winter wheat injury was more frequent with early vs. late postemergence (POST) applications and was influenced by wheat growth stage and mean, high, and low air temperatures before and after applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 8 publications
4
16
0
Order By: Relevance
“…At this time, the growth stage of the plants was Z21 to Z29. This is comparable with previous studies' application times, and confirms the tolerance of winter wheat to herbicides at this stage (Kelley and Peeper 2003;Hoskins et al 2005;Sikkema et al 2007). At this timing, the treatment of dicamba/MCPA/mecoprop consistently injured winter wheat and resulted in yield reductions at two locations in 2010.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…At this time, the growth stage of the plants was Z21 to Z29. This is comparable with previous studies' application times, and confirms the tolerance of winter wheat to herbicides at this stage (Kelley and Peeper 2003;Hoskins et al 2005;Sikkema et al 2007). At this timing, the treatment of dicamba/MCPA/mecoprop consistently injured winter wheat and resulted in yield reductions at two locations in 2010.…”
Section: Discussionsupporting
confidence: 88%
“…contrast to some studies done in fields with different herbicides applied under cold weather. Grey et al (2012), Hoskins et al (2005) and Kelley and Peeper (2003) all reported winter wheat injury when the herbicides were applied in cold conditions compared with warmer temperatures. These contrasting results could be due to the type of herbicides used, the air temperature and the growth stage of winter wheat at the time of application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few managerial options exist to selectively control undesirable grasses without negatively impacting desirable perennial grasses. Sulfosulfuron (1-(2-ethylsulfonylimidazo [1,2-alpyridin -3-ylsulfonyl)-3-(4,6-dimethoxypyrimidin-2-yl)urea) is a sulfonylurea herbicide that has been shown to selectively control the winter annuals downy brome (Bromus tectorum L.) (Geier et al 1998, Olsen et al 2000 and cheat (Bromus secalinus L.) (Kelley and Peeper 2003) and the troublesome rhizomatous pasture grasses quackgrass (Elytrigia repens L. Nevski) (Hageman et al 1996) and johnsongrass (Sorghum halepense L. Pers.)…”
Section: Rhizomatous Grasses Generally Experienced Greater Damage Frommentioning
confidence: 99%
“…Inadequate or delayed precipitation can reduce herbicide effectiveness and decrease weed control [1,4,11,[21][22][23]. Depending on soil type, high amounts of precipitation (i.e.…”
Section: Introductionmentioning
confidence: 99%